PEMANFAATAN MESIN PENGERING MINYAK DALAM PENINGKATAN PRODUKSI USAHA KERIPIK SINGKONG CAHAYA BANGKA - Yudi Oktriadi; Husman Husman; Masdani Masdani; Sukanto Sukanto; Achmad Afriadi; Febrian Alfarisyi; Fajar Abdallah (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2023)
Based on direct observation with partners, the problems faced are that in the process of drying the oil of cassava chips, they still use manual methods by drying them on a container for 15 minutes with the amount of cassava chips dried as much as 2 kg and this manual process still leaves oil on the cassava chips until they are marketed which in the future will make the cassava chips quickly unfit for consumption. The problem faced by the cassava chip business partner “Cahaya Bangka” is that they cannot be stored longer / not durable. The expected benefits of the partner can increase the amount of production, faster production time, and also produce more products and last longer/durable. The influence on sales is quite large because buyers are not brave enough to buy cassava chips in large quantities. The solution given to partners is to utilize a cassava chip oil dryer machine with the implementation method of providing short training on the operation and maintenance of the cassava chip oil dryer machine so that partners understand how to use and maintain the machine properly and correctly. With the cassava chip oil dryer machine, the drying process of cassava chips with a total of 10 kg of cassava chips in 4 minutes can increase the amount of production, the production process time becomes faster and the cassava chips become more durable than before.